John James Bezer (1816–1888) and his Autobiography of One of the Chartist Rebels of 1848 (1851) - Madeleine Pham-Thanh (Cahiers Victoriens et Edouardiens)
This paper focuses on J. J. Bezer’s Autobiography as a political intervention within the post-Chartist radical movement. In particular, it showcases his stylistic inventiveness, from the assumption that his idiolect contributes to the (re-)making of a popular counter-cultural sociolect. Most of all, it highlights the struggles of a popular, self-educated, unrepentant radical, to regain, through autobiographical reconstruction, the agency he was denied as a social and political marginal. While explaining the origin and nature of a working-man’s political commitment, and fleshing out the figure of the ‘Chartist rebel’ in popular imagination, Bezer’s narrative is an opportunity to substantiate the radical discourse as something drawn from lived experience. This political outlook oscillates between the individualistic ‘I’ of autobiography, and the generic subject indissociable from collective destiny. To a certain extent, Bezer’s political intervention and potential legacy must be balanced against the campaigning efforts of the somewhat anti-Chartist Christian Socialist, in which his (unfinished) Autobiography appeared by instalments. Ultimately, the text bears witness to the possibility for a popular radical voice to retain its independence, even with the marginalizing circumstances of publication and the general shift of militancy away from Chartist politics, in the post-1848 years.